Immunology and Homeopathy. 2. Cells of the Immune System and Inflammation. Issue 1 (2006) - Bellavite, Paolo; Conforti, Anita; Pontarollo, Francesco; Ortolani, Riccardo
Abstract : Here we describe the results of some experimental laboratory studies aimed at verifying the efficacy of high dilutions of substances and of homeopathic medicines in models of inflammation and immunity. Studies carried out on basophils, lymphocytes, granulocytes and fibroblasts are reviewed. This approach may help to test under controlled conditions the main principles of homeopathy such as 'similarity' of drug action at the cellular level and the effects of dilution/dynamization on the drug activity. The current situation is that few and rather small groups are working on laboratory models for homeopathy. Regarding the interpretation of data in view of the simile principle, we observe that there are different levels of similarity and that the laboratory data give support to this principle, but have not yet yielded the ultimate answer to the action mechanism of homeopathy. Evidence of the biological activity in vitro of highly diluted-dynamized solutions is slowly accumulating, with some conflicting reports. It is our hope that this review of literature unknown to most people will give an original and useful insight into the 'state-of-the-art' of homeopathy, without final conclusions 'for' or 'against' this modality. This kind of uncertainty may be difficult to accept, but is conceivably the most open-minded position now.